Inflammatory and apoptotic signalling pathways and concussion severity: a genetic association study. Issue 19 (2nd October 2018) - Mc Fie, Sarah; Abrahams, Shameemah; Patricios, Jon; Suter, Jason; Posthumus, Michael; September, Alison V.
ABSTRACT: The objective was to investigate the relationship between IL-1B rs16944, IL-6 rs1800795, and CASP8 rs3834129 genetic polymorphisms and concussion severity. Rugby players from high school, senior amateur, and professional teams completed a concussion severity questionnaire and donated a DNA sample. Participants (n = 163) were split into symptom severity groups around the median number and duration of symptoms. The frequency of participants with high symptom counts (more than five symptoms) increased across the IL-1B (C/C: 35%; C/T: 51%; T/T: 56%; P = 0.047) and the IL-6 (C/C: 31%; C/G: 44%; G/G: 58%; P = 0.027) genotypes. The C–C inferred interleukin allele construct frequency, created from combining the IL-1B and IL-6 genotype data, was lower in participants reporting a high symptom count (18%), compared to those with a low symptom count (fewer than six symptoms, 36%, P = 0.002). Similarly, the C–C inferred interleukin allele construct frequency was lower in those reporting prolonged symptom duration (more than one week, 16%), as opposed to short symptom duration (less than one week, 34%, P = 0.015). This study provides evidence of novel inflammatory pathway genetic associations with concussion severity, which supports the hypothesis implicating neuroinflammation in the development of concussion symptoms.